Analysis Of The Influence Of Compensation, Leadership Style And Professional Competency On Employee Turnover Intention Level With Organizational Commitment As A Moderation Variable In Rsu.Royal Prima Medan - Tarigan, Samuel; Ria Ginting, Rasinta; Romy, Elly; Purba, Kuras (International Journal of Science, Technology & Management, 2022)
This study aims to partially analyze the effect of compensation, leadership style and professional competence on the level of turnover intention of employees of RSU Royal Prima Medan, knowing the effect of compensation, leadership style and professional competence on the level of turnover intention of employees of RSU Royal Prima Medan. This research is a quantitative descriptive study with a questionnaire instrument conducted with a population of 87 permanent employees, the determination of the sample using a saturated sample so that the research sample is as much as. 87 people. The data analysis technique used is Path Analysis and is supported by Sobel Test calculations. The results of the research analysis show that based on the regression equation model 1 compensation, leadership style, professional competence have a positive and significant influence on employee turnover intention at Royal Prima Hospital Medan. Based on the regression equation model 2, compensation, leadership style, professional competence have a significant effect on turnover intention. Based on the regression equation model 1 and 2 that organizational commitment is able to intervene in the influence of compensation, leadership style and professional competence on the level of employee turnover intention of the Royal Prima General Hospital Medan.